Fertility characterization of soils at six research sites in NW Cameroon - Yamoah, C.F.; Ngueguim, M.; Ngong, C.; Osiname, O.A.; Tambi, E. (Springer, 1995)
Fertility capability of surface (0–20 cm) soils was evaluated at six sites in the North-West Cameroon highlands. Two main soil groups, designated as Classes A and B, were identified based on elevation. The Class A soils from low elevations (600–1178 m) had higher Ca, Mg, K, pH, sorbed less P and were lower in organic carbon and sesquioxides than the highland (> 1200 m) soils. Soil acidity (Al saturation > 30%) and high P sorption appeared to be the most limiting factors to crop production especially on the Class B soils where the Standard P Requirement exceeded 500 mg kg−1. Phosphorus sorption data were best described by the Freundlich equation. Amorphous aluminium was the most important determinant of solution P concentration (r = 0.85,p < 0.001) followed by soil organic carbon, (r = 0.80,p < 0.001) at high P rates. Nitrogen deficiency symptoms of maize were pronounced on the Class B soils. Consequently, crop growth and yield were lower on Class B than on Class A soils despite the high organic carbon in B. We hypothesize that the supply of high quality organic material (high in N and low in lignin and polyphenols) at site B through agroforestry and related cropping systems, would improve the fertility of the soil and crop yield.